2020
DOI: 10.1177/1129729820933396
|View full text |Cite
|
Sign up to set email alerts
|

Delamination of Acuseal early cannulation arteriovenous graft months after implantation

Abstract: Arteriovenous fistula is recommended, but arteriovenous graft is acceptable when a fistula is not possible. Acuseal is an early cannulation graft with a trilayer structure. Although primary patency rates of Acuseal appear to be similar to those of other standard grafts, few studies have investigated long-term results and complications. In our series, delamination of the wall structure occurred in 5.1% (6/115) by 21 months after Acuseal implantation. The causes could be divided into cannulation-related and cann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…A previous study demonstrated that two cases of the delamination occurred at the elbow joint, suggesting that the delamination might be due to the repeated movement of the elbow. 5 However, none of the delamination and dissections in the present study occurred at any joints. In the present study, the patients did not receive anti-platelet, anti-coagulation, or thrombolytic therapies except that only one patient was on aspirin treatment.…”
Section: Discussionmentioning
confidence: 59%
See 4 more Smart Citations
“…A previous study demonstrated that two cases of the delamination occurred at the elbow joint, suggesting that the delamination might be due to the repeated movement of the elbow. 5 However, none of the delamination and dissections in the present study occurred at any joints. In the present study, the patients did not receive anti-platelet, anti-coagulation, or thrombolytic therapies except that only one patient was on aspirin treatment.…”
Section: Discussionmentioning
confidence: 59%
“…We report four cases with dissections and delamination of the Acuseal AV graft. With the previous reported cases, [3][4][5] there are 12 cases of Acuseal graft dissection and delamination. In addition, there is a case report that described a dissection of a Hybrid AV graft.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations